(untitled) (Journal of the Bangladesh Agricultural University, 2016)
This research was carried out to study the air drying behavior of fresh and osmosed oyster mushroom. Three different temperatures (55, 60 and 65oC) were used to determine the effect of temperature on drying behavior of oyster mushroom in a mechanical dryer and an Arrhenius type relationship was developed from which activation energy value of 13.48 kcal/g-mole for fresh mushroom16.47 ,15.01and 4.19 kcal/g mole for mushroom osmosed at 12oC ,27oC and 45oC, respectively were found. Combined osmotic dehydration (in 20% salt solution) and air drying results in significantly higher (4 times) drying throughput compared to fresh mushroom. The values of proximate composition of fresh mushroom are 89.56, 3.83, 0.44, 0.91 and 5.26% moisture, protein, fat, ash, and total carbohydrate, respectively, while the corresponding values are 11.70, 31.5, 2.90, 5.92 and 47.98% moisture, protein, fat, ash and total carbohydrate for developed mushroom powder. J. Bangladesh Agril. Univ. 13(2): 307-314, December 2015